Analisis Perubahan Penggunaan Lahan Menggunakan Citra Sentinel-2 Di Kecamatan Percut Sei Tuan Tahun 2018 - 2022 - Nuel, Immanuel Sinabang; Klarita Dwijayanti Waruwu; Adesiana Sihombing; Adeline; Eni Yuniastuti (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
Population growth is a major driver of land cover/use change in general as it leads to economic development, which in turn requires land availability for other land uses, including infrastructure, services, industry and settlements. Using the symbolism of remote sensing satellites to plan land use over large areas is one approach that can be taken. This study aims to analyze land use change in Percut Sei Tuan District, Deli Serdang Regency, North Sumatra in the 2018-2022 period using Sentinel-2 satellite imagery. The method used is visual interpretation of satellite images with the help of ArcGIS software and multi-temporal spatial data comparison analysis. The results showed that there were 8 land use classes, namely water bodies, forests, rice fields, plantations, developed land, open land, clouds, and shrubs. Significant land use change occurred in built-up land which increased by 627 hectares (from 34% to 37% of the total area), while forest area decreased by 521 hectares (from 8% to 5%). These changes indicate land conversion from forest areas and other productive lands to built-up areas, driven by population growth and infrastructure needs. This study concludes that regular monitoring of land use change is necessary to support spatial planning and sustainable land resource management.